PEOPLE SMUGGLING, JUSTICE, LEGAL CERTAINTY AND UTILITY CONCEPT - Prisca, Pricillia (Fakultas Hukum Universitas Balikpapan, 2017)
Indonesia is not a state party to the 1951 Convention Relating to the Status of Refugees as well as its 1967 Protocol, but Indonesia is one of the countries with the greatest impact of refugees. There are many smuggler boats stranded in Indonesian water, bringing thousands of asylum seekers. These asylum seekers are often cheated by smugglers, they were boarded an improper vessels then stranded and being rejected. This article discusses the smuggling of people based on the perspective of legal theory of Gustav Radbruch.Key words: People smuggling, Migrant, Asylum seeker